Beclin1 Deficiency Suppresses Epileptic Seizures - Yang, Min; Lin, Peijia; Jing, Wei; Guo, Haokun; Chen, Hongnian; Chen, Yuanyuan; Guo, Yi; Gu, Yixue; He, Miaoqing; Wu, Junhong; Jiang, Xuejun; Zou, Zhen; et al. (Frontiers in Molecular Neuroscience, 2022)
Epilepsy is a common disease of the nervous system. Autophagy is a degradation process involved in epilepsy, and in turn, seizures can activate autophagy. Beclin1 plays a critical role in autophagy and participates in numerous physiological and pathological processes. However, the mechanism underlying the effect of Beclin1 on epilepsy remains unclear. In this study, we detected increased expression of Beclin1 in brain tissues from patients with temporal lobe epilepsy (TLE). Heterozygous disruption of beclin1 decreased susceptibility to epilepsy and suppressed seizure activity in two mouse epilepsy models. We further illustrated for the first time that heterozygous disruption of beclin1 suppresses excitatory synaptic transmission, which may be caused by a decreased dendritic spine density. These findings suggest for the first time that the regulation of Beclin1 may serve as a strategy for antiepileptic therapy. In addition, Beclin1 participates in synaptic transmission, and the development of dendritic spines may be a biological function of Beclin1 independent of its role in autophagy.